2018
DOI: 10.1177/0145721718765947
|View full text |Cite
|
Sign up to set email alerts
|

Positive Health Benefits of Peer Support and Connections for College Students With Type 1 Diabetes Mellitus

Abstract: Purpose The purpose of this study is to examine the characteristics and health outcomes of college students with type 1 diabetes mellitus (T1DM) as it relates to membership in a local university-based diabetes student organization. Methods This descriptive, correlational research design is a secondary analysis of data. The sample consisted of nationally representative young adults in college (n = 317) between 18 and 30 years of age who were diagnosed with T1DM. Data were collected during April 2017 using a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…This theme captures how students with T1D see diabetes as a part of themselves, and even come to appreciate the responsibility they have developed over time, as a result of having to manage their T1D. As observed by Saylor et al (2018), participation in university-led diabetes student clubs provides individuals living with T1D with direct diabetes-specific support during emerging adulthood while in this new environment. These clubs could be adapted to provide initial workshops to both parents and students regarding the transition and the individual themselves taking sole responsibility with this potential peer support.…”
Section: Discussionmentioning
confidence: 97%
“…This theme captures how students with T1D see diabetes as a part of themselves, and even come to appreciate the responsibility they have developed over time, as a result of having to manage their T1D. As observed by Saylor et al (2018), participation in university-led diabetes student clubs provides individuals living with T1D with direct diabetes-specific support during emerging adulthood while in this new environment. These clubs could be adapted to provide initial workshops to both parents and students regarding the transition and the individual themselves taking sole responsibility with this potential peer support.…”
Section: Discussionmentioning
confidence: 97%
“…Alterations in sleep patterns may change during their col-lege campus living due to erratic schedules and new found independence [3,4,38]. According to the Centers for Disease Control and Prevention (CDC), in the Unites States, 32% of EYA's (18-24 years old) sleep less than 7 h per night and among all adults there is a higher prevalence of shorter sleep duration among non-Caucasians [39].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The College Diabetes Network is a non-profit organization that focuses on provid-ing college students with peer support with local chapters on campus. Previous research has shown that CDN members may be more involved in their own diabetes management, particularly if they have a peer-led CDN chapter on their respective college campus [38].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Overall summaries of outreach platform acceptability among valid cases were characterized descriptively. Finally, sample representativeness was assessed by comparing descriptive characteristics of valid cases to user features derived from GA and to previously described characteristics of the CDN source population; 47 differences were assessed using appropriate bivariate tests.…”
Section: Methodsmentioning
confidence: 99%